What Comes from Cytology Diagnosis: A Comprehensive Epidemiological Retrospective Analysis of 3068 Feline Cases - Paula Brilhante-Simões; Ricardo Lopes; Leonor Delgado; Ana Machado; Augusto Silva; Ângela Martins; Ricardo Marcos; Felisbina Queiroga; Justina Prada (Veterinary Sciences)
This study evaluated diagnostic trends and the overall utility of cytology in feline patients through the analysis of a large, multicentric dataset from Portugal. A retrospective review of 3068 cytological cases from 130 veterinary practices was conducted, with samples categorised by anatomical location and lesion type. Diagnostic outcomes were statistically assessed, revealing an overall success rate of 66.20%. The highest diagnostic yields occurred in fluid samples (83.48%), glandular tissues (76.67%), and mucous membranes (75.81%), followed by organ-based samples (67.79%), miscellaneous tissues (66.98%), cutaneous/subcutaneous nodules (62.16%), and lymph nodes (57.93%). Neoplastic lesions showed age-associated prevalence, being more common in older cats, with epithelial and melanocytic lesions more frequent in females and round cell/mesenchymal lesions predominating in males. Non-diagnostic samples (33.80%) primarily resulted from insufficient cellularity or suboptimal quality, though no significant correlation existed between diagnostic success and clinical setting. This study underscores that cytology remains a fundamental diagnostic tool in feline medicine, particularly when combined with proper sampling techniques and complementary diagnostic methods, and reinforces its value in clinical decision-making, thereby supporting its broader utilisation in routine veterinary practice.